Automation and computerization of the articular and Ritchie’s indexes calculation - W. Troise Rioda; A. Nervetti (Reumatismo, 2003)
Compilation and calculation of some articular indexes is time consuming. Therefore the authors present a data base for automatic compilation and calculation of articular and Ritchie’s indexes. Moreover the program allows to determine the number of the swollen and painful joints.